1956
DOI: 10.1017/s0021859600030318
|View full text |Cite
|
Sign up to set email alerts
|

The maternal influence on size in sheep

Abstract: With Plates 1-3 and Sixteen Text-figures)Factors which affect the growth of the young animal are of great economic importance in animal production. In the past, much experimental work has been concerned with the effect on the growth of the young animal of different environmental factors. Many of these factors do not, however, affect the development of the young animal directly, but rather act on its maternal environment. Thus, much is known of the factors which affect the milk secretion of the female and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

1959
1959
2004
2004

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 37 publications
(45 reference statements)
5
43
1
Order By: Relevance
“…By using various techniques (e.g. reciprocal matings or embryo transfers between breeds), it has been shown that the maternal genotype has a profound influence on fetal growth (Walton & Hammond, 1938;Venge, 1950;Hunter, 1956;Joubert & Hammond, 1958). In addition, the maternal system appears to have a limited ability to support fetal growth (Barcroft, 1946;McKeown & Record, 1953;Alexander, 1964;Anderson et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…By using various techniques (e.g. reciprocal matings or embryo transfers between breeds), it has been shown that the maternal genotype has a profound influence on fetal growth (Walton & Hammond, 1938;Venge, 1950;Hunter, 1956;Joubert & Hammond, 1958). In addition, the maternal system appears to have a limited ability to support fetal growth (Barcroft, 1946;McKeown & Record, 1953;Alexander, 1964;Anderson et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…MATERNAL effects on adult size have been reported in several specie& of mammal (Walton and Hammond, 1938;Hunter, 1956;Joubert and Hammond, 1958;Brumby, ig6o). Their existence in birds is less certain, partly because the male (homogametic sex) is more troublesome to keep, and economically less useful, than the female.…”
Section: Introductionmentioning
confidence: 98%
“…This fact was shown dramatically by Walton and Hammond [1938] who made reciprocal crosses between a very large breed of horses, the Shire, and a small breed of horses, the Shetland, and compared the foals. A similar study was conducted by Hunter [1956] who crossed the large Border…”
Section: Prenatal Growth and Developmentmentioning
confidence: 84%